Differential Marking In Kinande - Irimia, Monica Alexandrina; Schneider-Zioga, Patricia (My University, 2021)
This work presents newly-discovered data involving differential marking in the Bantu language Kinande (JD42), which affects three classes: (i) goals and sources; (ii) predicative possession; (iii) external possession. These patterns reveal important insights into the nature of differential marking in Bantu. First, typical differential marking features like animacy, definiteness, and person can involve a morphological difference on a dependent nominal in Kinande, and is not only restricted to the better studied agreement/concord cross-indexing on the verb, which is familiar from work on other Bantu languages. Secondly, Kinande differential marking has non-trivial syntactic correlates and provides further support for nominal licensing inside vP in Bantu languages. Thirdly, Kinande provides evidence for more than one structural source of differential marking, supporting at least three types of syntactic analyses for this phenomenon.
Keywords: Kinande; Differential marking; Bantu language